Pengaruh Pemberian Kombinasi Metformin Dan Oksigen Hiperbarik Terhadap Jumlah Fibroblas Dan Ketebalan Kolagen Dalam Penyembuhan Luka Pada Tikus Putih - Wahyu Dewi Tamayanti; Bemadette Dian Novita Dewi; Imelda Theodora (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2018)
Metformin is used in patients with type 2 DM who had a chronic hyperglycemia caused by insulin resistance. DM patients also suffered from hypoxia condtion of lacking oxygen in the tissues.This study was aimed to identify the effect of combination therapy of metformin and hyperbaric oxygen to increase the number of fibroblasts and collagen thickness in thePseudomonas aeruginosa-infected tissue in male Wistar rats with hyperglycemia. This study used alloxan 8% (w/v) that was injected intramuscular, anaerobic bacteria Pseudomonas aeruginosa in the injured area, metformin of 45mg/kgBB dose, and hyperbaric oxygen therapy at 2.4 ATA given 3 times 30 minutes respectively with 5 minutes interval for 5 consecutive days. Male Wistar rats (Rattus norvegicus) were divided into five groups:KN- was the group of normal Wistar rats;KDM- was the group with alloxan induction;KI -was the group with alloxan induction and infected by Pseudomonas aeruginosawithout treatment;KU1 - was the group induced by alloxan, infected by Pseudomonas aeruginosa, and treated by metformin; and KU2 – was the group that induced by alloxan, infected by Pseudomonas aeruginosaand treated by combination therapy ofmetformin and hyperbaric oxygen. Skin tissue was taken on the termination and HE stained to analysed the number of fibroblast and sized the collagen. Data obtained was statistically analysed by One way anava with a significant level of 5%. The result confirmed that combination therapy of metformin and hyperbaric oxygen increases the number of fibroblasts and collagen thickness in the wound of male hyperglycemic Wistar rats that Pseudomonas aeruginosa-infected